Non-Verbal Communication in Greetings in Chinese: a Pedagogical Proposal - Qu Lu, Xianghong (Sinología hispánica. China Studies Review, 2019)
Due to the problems detected in the practice of teaching Chinese as second Language, on the other hand with the theoretical advances both in nonverbal communication and in pedagogy, especially in that of Chinese language, we began to reflect on the importance of the nonverbal language in intercultural communications. It is found that it necessary to make a theoretical and practical proposal for the integration of nonverbal communication into the Chinese language teaching materials, for the purpose of improving our students’ communication and the comprehension on the culture and society of China. In this goal, the present work consists in the analysis of nonverbal signs used in some specific communicative contexts in Chinese related to the topic of “greetings”, and in the identification of those nonverbal signs that can more easily cause errors of interpretation in the students, mainly by questionnaire, interviews and bibliographic review. Finally, based on the results of our study, we present a concrete pedagogical proposal composed by five activities, in order to offer a complementary material that could help the students to avoid misinterpretations in spoken or written context that block and distort the transmission of messages.